The Influence of Trust, Security and Brand Image Factors on the Decision to Donate Online on the Crowdfunding Platform Kitabisa.com. - muhammad fazil shelby; Muhammad Hafizh (Komunitas Dosen Indonesia, 2024)
Online donations through crowdfunding platforms are becoming increasingly popular in Indonesia, especially with the advancement of technology and the growing access to the internet. One of the platforms widely used for online donations is Kitabisa.com. This platform allows individuals and organizations to raise funds easily and quickly, as well as providing opportunities for the public to participate in various charitable and social activities. This study aims to determine the influence of trust, security, and brand image on the decision to donate on Kitabisa.com. In this study, a quantitative approach was used with a sample of 100 respondents selected randomly. The data collected through a Likert scale questionnaire were then analyzed using multiple linear regression methods, with the help of Eviews version 10 software. Trust is considered the main factor influencing donation decisions, as donors must be assured that the funds they donate will be used according to the promised objectives. Security is also an important factor, given that financial transactions conducted online must have adequate protection to ensure the donors' personal and financial data remain secure. Additionally, the brand image of Kitabisa.com as a trusted and well-known platform also plays a role in attracting public interest in donating. Understanding these factors is crucial to enhancing trust and participation in online donations. The results of the study show that trust, security, and brand image significantly influence the decision to donate on Kitabisa.com. By understanding and effectively managing these factors, Kitabisa.com can continuously improve its strategies to attract more donors, build stronger trust among users, and ultimately increase participation in charitable and social activities in Indonesia.